How to do a systematic literature review - M. Papadopoulos; P. Rheeder (AOSIS, 2000)
Physiotherapists, whether serving individual patients or populations, always have to sought to base their decisions and actions on the best possible evidence. In making choices, health professionals may benefit from structured summaries of the options and outcomes, systematic reviews of the evidence and recommendations regarding the best choices. The aim of this paper is to present guidelines on how to conduct a systematic review. The structure and content of a systematic review are being discussed, following a step-by-step approach.